Small element array algorithm for correcting phase aberration using near-field signal redundancy. Part I : Principles - Li, Yue (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2000)
A near-field, signal-redundancy algorithm for measuring phase-aberration profiles has been proposed previously. It is designed for arrays with a relatively large element size for which relatively narrow beams are transmitted and received. The algorithm measures the aberration profile by cross-correlating signals collected with the same midpoint position between transmitter and receiver, termed common midpoint signals, after a dynamic near-field delay correction. In this paper, a near-field signal-redundancy algorithm for small element arrays is proposed. In this algorithm, subarrays are formed of adjacent groups of elements to narrow the beams used to collect common midpoint signals and steer the beam direction, so that angle-dependent, phase-aberration profiles can be measured. There are several methods that could be used to implement the dynamic near-field delay correction on common midpoint signals collected with subarrays. In this paper, the similarity between common midpoint signals collected with these methods is also analyzed and compared using a so-called corresponding-signal concept. This analysis should be valid for general target distributions in the near field and wide-band signals.